Advances in Anti-Tumor Treatments Targeting the CD47/SIRPα Axis - Zhang, Wenting; Huang, Qinghua; Xiao, Weiwei; Zhao, Yue; Pi, Jiang; Xu, Huan; Zhao, Hongxia; Xu, Junfa; Evans, Colin E.; Jin, Hua (Frontiers in Immunology, 2020)
CD47 is an immunoglobulin that is overexpressed on the surface of many types of cancer cells. CD47 forms a signaling complex with signal-regulatory protein α (SIRPα), enabling the escape of these cancer cells from macrophage-mediated phagocytosis. In recent years, CD47 has been shown to be highly expressed by various types of solid tumors and to be associated with poor patient prognosis in various types of cancer. A growing number of studies have since demonstrated that inhibiting the CD47-SIRPα signaling pathway promotes the adaptive immune response and enhances the phagocytosis of tumor cells by macrophages. Improved understanding in this field of research could lead to the development of novel and effective anti-tumor treatments that act through the inhibition of CD47 signaling in cancer cells. In this review, we describe the structure and function of CD47, provide an overview of studies that have aimed to inhibit CD47-dependent avoidance of macrophage-mediated phagocytosis by tumor cells, and assess the potential and challenges for targeting the CD47-SIRPα signaling pathway in anti-cancer therapy.